(untitled) (Journal of Scientific Research, 2012)
The immunostimulating activity of 70% ethanololic extract of P. nigrum L. was investigated by measuring the production of immunoglobulin M (IgM) and the proliferation of murine splenic cells in vitro. The production of IgM in cultured supernatants was determined by an enzyme-linked immunosorbent assay (ELISA) and proliferation of cells was measured by 3-(4,5-dimethylthiazol-2-y)-2,5-diphenylterazolium bromide (MTT) assay. The extract at the doses of 0.01 and 0.1 mg/ml significantly augmented the production of polyclonal IgM production (0.3206 and 0.5014 µg/ml, respectively) compared to control (0.1465 µg/ml). No dose of the extract could remarkably increase the proliferation of splenocytes. Thus, the present study clearly demonstrates the immunostimulating activity of ethanololic extract of Piper nigrum; exhibited mainly by the differentiation of B cells to plasma cells rather than proliferation of splenocytes. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10485 J. Sci. Res. 4 (3), 751-756 (2012)